PEMBUATAN WEBSITE COMPANY DENGAN FITUR ANTRIAN ONLINE DAN PENDAFTARAN PASIEN RAWAT JALAN DI PUSKESMAS WRINGIN BONDOWOSO - Sitti Fa'Isil Karomah; Andri Permana Wicaksono; Mochammad Choirur Roziqin; Erna Selviyanti (Politeknik Negeri Jember, 2022)
The patient registration system at the Wringin Bondowoso Public Health Center is still done manually starting from providing queue numbers, calling queue numbers to making KIB and reports. Officers prepare queue papers every day and patients often lose being carried home and officers have difficulty finding patient data during the registration process. In addition, manual registration is prone to human error, and manually counting patient visits over a period of time may lead to inaccurate information. The purpose of this study is to create a company website with online queuing features and outpatient registration at Wringin Bondowoso Public Health Center. The method used in this research is waterfall. The stages of the waterfall method are requirements analysis, system design, system creation and system testing. The result of this study is a company profile website that helps patients get information related to puskesmas and register online queues. The results of this study are also an outpatient registration information system that can facilitate officers in the process of calling queues, printing queue numbers, recording patient data, patient visits, and making MCH and reports.